A fundamental investigation of reinforced concrete beams subjected to close-in explosion. Issue 2 (June 2018) - Nagata, Makoto; Beppu, Masuhiro; Ichino, Hiroyoshi; Matsuzawa, Ryo
This study investigates a reinforced concrete beam subjected to a close-in explosion. In a series of tests, the scaled distance was varied from 0.045 m/kg 1/3 (contact) to 0.30 m/kg 1/3 . The measurement parameters were failure state, pressure distribution, residual displacement at the center of the beam, and reaction force. The experimental results showed that the pressure waveform closer to the center of the reinforced concrete beam had considerable peak pressure and a sharp rise-time. Moreover, the loading duration at the ends of the beam was increased as compared to that at the center. The intensity of the local failure region and the residual displacement at the center of the beam increased with decrease in the scaled distance. Referring to previous studies on failure prediction of a reinforced concrete slab and beams subjected to close-in explosion, their prediction methods for local failure were compared to test results. Numerical simulations were performed to investigate failure characteristics of the reinforced concrete beam. The numerical results demonstrated that the peak pressure and impulse in the central part were considerably high as the scaled distance decreased. The numerical simulations effectively reproduced failure characteristics of the reinforced concrete beam.